2014
DOI: 10.1007/s00018-014-1739-4
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic control of oocyte development: linking maternal nutrition and reproductive outcomes

Abstract: Obesity, diabetes, and related metabolic disorders are major health issues worldwide. As the epidemic of metabolic disorders continues, the associated medical comorbidities, including the detrimental impact on reproduction, increase as well. Emerging evidence suggests that the effects of maternal nutrition on reproductive outcomes are likely to be mediated, at least in part, by oocyte metabolism. Well-balanced and timed energy metabolism is critical for optimal development of oocytes. To date, much of our unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
102
0
7

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(119 citation statements)
references
References 295 publications
(274 reference statements)
3
102
0
7
Order By: Relevance
“…Exposing females to a high-fat or low-protein diet, or inducing them into a diabetic-like state using streptozocin, is associated with widespread effects on the health of their offspring [96][97][98][99]. These outcomes are observed even when embryos at the blastocyst stage are transferred to pseudopregnant recipients, ruling out effects on the uterine environment as the origin of the effect.…”
Section: Intergenerational Inheritance and Potential Mechanismsmentioning
confidence: 93%
“…Exposing females to a high-fat or low-protein diet, or inducing them into a diabetic-like state using streptozocin, is associated with widespread effects on the health of their offspring [96][97][98][99]. These outcomes are observed even when embryos at the blastocyst stage are transferred to pseudopregnant recipients, ruling out effects on the uterine environment as the origin of the effect.…”
Section: Intergenerational Inheritance and Potential Mechanismsmentioning
confidence: 93%
“…The processes of oocyte maturation and potentially the accumulation of its epigenetic characteristics on histones and DNA depend, in part, on the milieu of the follicular fluid in which oocytes are suspended. 67 Just as maternal obesity and stress have been associated with altered follicular fluid composition ( e.g ., elevated levels of intra-oocyte oxidative stress 68,69 ), it also may be possible that the oocyte milieu could be altered by the biological ( e.g ., endocrine, immune, metabolic) sequelae of CM exposure. So far, to our knowledge there is no empirical evidence substantiating this claim.…”
Section: Mechanisms Of Intergenerational Transmission Of Childhood Mamentioning
confidence: 99%
“…Pyruvate regulated both the intracellular redox status and energy supply at a higher concentration but regulated only energy supply at a lower concentration to inhibit oocyte aging9. Well-balanced and timed glucose metabolism need enough and timely glucose transport in oocytes10. It was found that NEURONATIN (NNAT) was an important protein to regulate glucose transport 1(GLUT-1) by activating PI3K-Akt2 signaling pathway11.…”
mentioning
confidence: 99%